Developing Writing Test Eptic (English Proficiency Test for Islamic Community) Based on Islamic Content - Elfi Elfi; Reni Susanti (Institut Agama Islam Negeri Palopo, 2021)
The problem discussed in this study is that there is no writing test based on Islamic values. The purpose of this study was to determine the analysis of student needs for the EPTIC (English Proficiency Test for Islamic Community) writing test, and to develop a writing test based on Islamic values (Writing test EPTIC). This research is a development research (R & D). Informants from this study were English Language Tadris (TBI) students in the 5th semester of the 2019/2020 academic year, totaling 45 people. The informant selection technique is total sampling. The instrument used is a questionnaire to determine the analysis of student needs for the EPTIC writing test. The research procedure used is the ADDIE model, which is to analyze, design and develop an EPTIC writing test product based on Islamic values. Furthermore, to analyze the data, the researcher uses the theory of Miles and Huberman (1994) by reducing the data, presenting the data, and verifying the data and draw a conclusion. To validate the product, the researcher used a validation sheet from riduan theory (2007) which consisted of five categories, namely very valid, valid, less valid, invalid, and very invalid. The results showed that, 90.9% of students needed an EPTIC writing test based on Islamic values. After being validated by the validator, the EPTIC writing test based on Islamic values developed was very valid with a score of 93.13.